Samarium doped ceria (SDC) electrolyte modification by sintering aids addition to reducing sintering temperature: a review - Zolhafizia, J.; Rahman, H.A.; Zakaria, H.; Hassan, S.; Mahzan, S.; Ismail, A.; Ariffin, A.M.T.; Tukimon, M.F; Yusof, U.A.; Azham Azmia, M. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The solid oxide fuel cell (SOFC) is a promising technology with specific characteristics for generating electricity by using hydrogen and oxidant as fuel. Typically, SOFC’s use Samarium doped Ceria (SDC) as an electrolyte material as the ionic conductivity of SDC was better at lower operating temperatures which are below than 700°C that making it a good option for low and moderate temperature applications for SOFC. However, SDC electrolytes are cannot be densified below 1500°C. If a densified ceria-based electrolyte can be prepared at lower temperatures it can be co-sintered with another electrode component. This simplifies the fabrication process and reduces the cost. Other than that, it can help with porous electrode microstructure control and avoiding phase diffusion and chemical interaction problems. As a result, decreasing the sintering temperature may be another step toward commercialising SOFC technology. The modification of electrolyte by adding sintering aid was found as an effective method to lowering the sintering temperature. This paper, therefore, focuses on reviewing the attempts made to modify SDC electrolyte by adding sintering aid (Li2O, CoO, CuO and FeO) in order to lowering sintering temperature. The studies related to temperature reduction, relative density, the microstructure of grains and conductivity of electrolyte was critically reviewed.